2008
DOI: 10.1037/1091-7527.26.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric asthma and problems in attention, concentration, and impulsivity: Disruption of the family management system.

Abstract: Rationale-This study assesses the relationships between ADHD symptoms, specific family asthma management domains, and pediatric asthma morbidity.Methods-Participants were 110 children with asthma and a respective parent (ages 7-17, X = 11.6 years, 25% ethnic/racial minority). Parents completed measures of asthma morbidity and report of child ADHD symptoms. Children completed measures of attention, concentration, and impulsivity. Families participated in the Family Asthma Management System Scale (FAMSS) intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
1
13
0
1
Order By: Relevance
“…We observed that higher levels of secrecy were associated with higher levels of negative affect, which, in turn, explained the association of secrecy with nightly awakenings and daytime asthma symptoms. These findings support a large body of work on youth emotional adjustment and asthma severity (3) and highlight the idea that affective processes may serve as key mediators of youth social experiences on asthma outcomes (52). …”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We observed that higher levels of secrecy were associated with higher levels of negative affect, which, in turn, explained the association of secrecy with nightly awakenings and daytime asthma symptoms. These findings support a large body of work on youth emotional adjustment and asthma severity (3) and highlight the idea that affective processes may serve as key mediators of youth social experiences on asthma outcomes (52). …”
Section: Discussionsupporting
confidence: 80%
“…Asthma can influence developmental outcomes, increasing vulnerability for emotional and behavioral difficulties, which are exacerbated in youth facing socioeconomic adversity (2, 3). Research suggests that psychosocial stressors involving challenges in affiliating with others are associated with exacerbation of pediatric asthma symptoms and greater functional impairment (3). For example, family conflict, youth oppositional behaviors, and difficulties in getting along with peers show robust associations with asthma severity, such as more frequent experiences of asthma attacks (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ADHD is characterized, according to DSM‐IV by hyperactivity–impulsivity (HI) and inattention (IN) with a prevalence of 3–5% in school‐aged children (2). Several previous studies, including a meta‐analysis (3), have shown an association between asthma and ADHD symptoms (4–6), although studies do exist where a relationship was not found (7, 8). One study of 102 253 children from the National Survey of Children’s Health showed a twofold increased prevalence of ADHD among children with asthma and even higher rates of ADHD among children with severe asthma (9).…”
mentioning
confidence: 99%
“…We found that some families adopt certain management behaviors that may change during the course of the disease, and others remain with the same characteristics and behaviors. As it has already been observed in studies in the context of chronic disease, such behaviors can influence how the family go through the experience and even the child's prognosis (2)(3)(4)(5)(6) . Recently, there is growing interest in learning the different styles of family management in various disease situations.…”
Section: Introductionmentioning
confidence: 99%